Pengaruh Substitusi Tepung Labu Kuning (Cucurbhita Moschata)Terhadap Kadar Proksimat Dan Kerenyahan Biskuit - DEWI RATNASARI, Dewi; , Eni Purwani, S.Si., M.Si; , Pramudya Kurnia, STP, M.Agr (2015)
FLOUR THE INFLUENCE OF THE SUBSTUTION OF PUMPKIN (Curbita Moschata) OF LEVELS OF THE PROXIMATE AND CRUNCHY BISCUIT. Background: Pumpkin is source local food that can be an alternative to reduce comsumtion of wheat, because at the quantity has more and pumkin is source local food that has high vitamins A, B,and C and carbohydrate. Purpose: To know the proximate compotitions and level of crunchy biscuit with different substitution of pumpkin. Methods: This research is experimental research that using pumpkin that be make flour. The research is done of food laboratory UGM. Methode of analyzing using stastical one way anova test and p< 0,05 and followed LSD. Results: Pumpkin of biscuit with substitution 15% has a the highest water content (6,65%). Pumpkin of biscuit with substitution 15% has a the highest ash content (1,72%) and has the highest fat content (19,68%). Pumpkin of biscuits with substitutions 0% has highest protein content (6,37%), has highest carbohydrate content (176,21%) and has the crunchiest biscuit (19,09 N). Conclusion: There is different and the level crunchy pumpkin biscuit with different substitution (0%,5%,10%,15%). Suggestion: The need for further about substitution pumpkin that is not limited to the biscuit, it for example product of noodles and cake to add diversity of food product based pumpkin. Keyword: Biscuit, compotition proximate, pumpkin, the level of crunchy. Bibliography: 43 (1996 - 2014).